Links Between Metabolic and Structural Changes in the Brain of Cognitively Normal Older Adults: A 4-Year Longitudinal Follow-Up - Castellano, Christian-Alexandre; Hudon, Carol; Croteau, Etienne; Fortier, Mélanie; St-Pierre, Valérie; Vandenberghe, Camille; Nugent, Scott; Tremblay, Sébastien; Paquet, Nancy; Lepage, Martin; Fülöp, Tamàs; Turcotte, Éric E.; et al. (Frontiers in Aging Neuroscience, 2019)
We aimed to longitudinally assess the relationship between changing brain energy metabolism (glucose and acetoacetate) and cognition during healthy aging. Participants aged 71 ± 5 y underwent cognitive evaluation and quantitative positron emission tomography (PET) and magnetic resonance imaging (MRI) scans at baseline (N=25) and two (N=25) and four (N=16) years later. During the follow-up, the rate constant for brain extraction of glucose (Kglc) declined by 6-12% mainly in the temporo-parietal lobes and cingulate gyri (p ≤ 0.05), whereas acetoacetate extraction and utilization remained unchanged in all brain regions (p ≥ 0.06). Over the four years, cognitive results remained within the normal age range but the main age-related decline was observed in processing speed. Kglc in the caudate was directly related to performance on several cognitive tests (r = +0.41 to +0.43, all p ≤ 0.04). Peripheral insulin resistance assessed by the HOMA-IR was significantly inversely related to Kglc in the thalamus (r = -0.44, p = 0.04) and in the caudate (r = -0.43, p = 0.05), and also inversely related to executive function, attention and processing speed (r = -0.45 to -0.53, all p ≤ 0.03). We confirm in a longitudinal setting that the age-related decline in brain glucose extraction is directly associated with declining performance on some tests of cognition but does not significantly affect brain acetoacetate extraction.